Application of the SOLE (Self Organized Learning Environments) Learning Model in Improving Student English Learning Outcomes - Rahayu, Arum Putri (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
The aim from this study is to improve English skills mastery of students by applying the SOLE (Self Organized Learning Environment) learning model. The study conducted qualitative research by case study type. The research result showing the improvement of students self-confidence in explaining their idea towards other students, after getting the stimulus of challenging question from the teacher.